Construction Costs and Housing Prices: Impact of Goods and Services Tax - Zainal, Rozlin; Teng, Teoh Chai; Mohamed, Sulzakimin (International Journal of Economics and Financial Issues, 2016)
It was expected that construction capital costs and housing property prices will increase following the implementation of GST in Malaysia on 1 April 2015. Therefore, this study examines the impact of GST on the construction capital costs and its influences towards the housing developers and housing property prices. This study also aims to highlight the developers' point of view regarding GST and the housing prices. Moreover, the discussion on future proposal of initiatives for benefits of developers and consumer. The findings are obtained from a survey where 36 housing developers and an experienced property consultant under the employment of Henry Butcher (International Asset Consultant) in Penang, Malaysia are the respondent. It was concluded that building materials and land acquisition are the major construction capital costs affected by the GST implementation. Subsequently, capital flow turnover is the post and significant consequence that developers now face which led to an increment of housing property prices. Hence, the end buyers are the ones who feel the impact of price increment and the government plays the central role in this scenario. Keywords: Construction Cost, Goods and Services Tax, Housing Prices JEL Classifications: L74, R31